Calculation Method of the Meshing Force of Cycloid Pinwheel with Considering Position and Radius Combined Random Error of Pin - Wang Qiliang Zhu Min Chen Xinwen Ye Xiaofen Meng Yongshuai Gong Feng (Jixie chuandong)
Cycloidal pinwheel planetary transmission is a kind of transmission method commonly used in industry. It is difficult to accurately process the position and the radius of pins as theoretical values when cycloidal wheels and pin wheels are machined and assembled. They are random variables that fluctuate in the range of machining errors. This will affect the meshing of the cycloidal pinwheel. The meshing force affects the accuracy and stability of cycloidal pinwheel planetary transmission，and then affects transmission error. A method for calculating the meshing force of cycloidal pinwheel based on Hertz formula is presented. It is proposed that there exists a combined random error of position and radius of pins during the meshing of cycloidal gear and pins. The formula for calculating the relative rotation angle considering this random error is deduced. The meshing force with considering the random error is further studied with an example. And the influence of meshing force on transmission error is analyzed. The computational model can be used for reference in the transmission accuracy design of robot high precision reducer.